Maillages, interfaces, réseaux transfrontaliers, de nouveaux enjeux territoriaux de la santé - François, Moullé; REITEL, Bernard (S@nté en contextes, 2021)
More than ever, care policies have become crucial issues in many European countries due to demographic ageing and technological developments, but also due to the emergence of a new approach by health actors that transforms patients into users, citizens or clients, as the case may be. In this context, the issue of unequal access to care has become a shared concern in Europe, particularly socio-spatial inequalities. We are observing, on the one hand, the development of governance systems by health authorities and, on the other hand, the mobilisation of networks, be they technical, social or territorial, which constitute useful resources for public authorities and health actors in seeking to respond to management issues and patient demands. The issue of the territorialisation of health is questioned through the networking of territories, state borders, the relations between territories and networks, and the effects or not in terms of the attenuation of socio-spatial inequalities. The link between health and territory is a good indicator of the changes in our societies and the way in which public authorities meet the challenges through the implementation of appropriate policies.